Academic evaluation protocol for monitoring modalities of use at an Automatic Control Laboratory: Local vs. remote (2013)
This article describes an Academic Evaluation Protocol (AEP) designed and implemented in order to monitor various modalities of using an Automatic Control Laboratory by analyzing the quality of work that can be obtained from a specific student group when the proposed experimental practice is being conducted according to a particular type of lab-work modality. To serve this purpose, the types of use-modalities associated to different lab-works are classified as follows: Local Real Laboratory (RL), Remote Laboratory (R@L) and Local plus Remote Laboratory (RL+R@L). To estimate how a specific lab-work modality impacts upon the development of an experimental practice, parameters such as average utilization time and the ABET-Indicators are used. The results obtained from this pedagogical instrument are analyzed by various means, namely the ANOVA Test, a Descriptive Statistical Technique and Wilcoxon Testing. The findings reveal that the student groups involved in experimental lab-practices following the RL and RL+R@L modalities achieve better performance (when conducting the automatic control laboratory) than the student groups served with the remote system only. The analysis performed indicates that there is no statistical difference between working at the Local Laboratory (RL) or at a Local plus Remote Laboratory (RL+R@L). As a result, the use of the remote system combined with the local one does not improve significantly the ABET score, ruling out the idea that by placing special interest in using only the remote system, an improvement in students' comprehension is achieved. © 2013 TEMPUS Publications.